Ультразвуковая обработка сталей и сплавов: учебное пособие - Панин А. В. Алексей Викторович; Клименов В. А. Василий Александрович; Перевалова О. Б.; Ковалевская Ж. Г. Жанна Геннадьевна; Казаченок М. С. Марина Сергеевна; Панина А. А. Александра Анатольевна; Синякова Е. А. (Томск, Изд-во ТПУ, 2019)
Заглавие с титульного экрана